2019
DOI: 10.1186/s11671-019-3167-8
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanomaterials for the Treatment of Heavy Metal-Contaminated Water and Environmental Remediation

Abstract: Nanotechnology is an advanced field of science having the ability to solve the variety of environmental challenges by controlling the size and shape of the materials at a nanoscale. Carbon nanomaterials are unique because of their nontoxic nature, high surface area, easier biodegradation, and particularly useful environmental remediation. Heavy metal contamination in water is a major problem and poses a great risk to human health. Carbon nanomaterials are getting more and more attention due to their superior p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(103 citation statements)
references
References 155 publications
1
101
0
1
Order By: Relevance
“…The flasks were sealed and placed in a thermostated shaker operated at 150 rpm and allowed to attain equilibrium. The kinetics of adsorption experiments were conducted at a different time interval (10,20,30,40,50, and 60 min). The effect of temperature was investigated at different temperatures (30,40, and 50 C).…”
Section: Batch Adsorption Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The flasks were sealed and placed in a thermostated shaker operated at 150 rpm and allowed to attain equilibrium. The kinetics of adsorption experiments were conducted at a different time interval (10,20,30,40,50, and 60 min). The effect of temperature was investigated at different temperatures (30,40, and 50 C).…”
Section: Batch Adsorption Studiesmentioning
confidence: 99%
“…The surface area of adsorbent is also very vital to the adsorption process as porous material with a high surface area may be employed as adsorbent [49]. The high adsorption capacity of CNTs is attributed to their large surface area [50]. The BET analysis revealed that the surface area of as-produced MWCNTs, PMWCNTs and FMWCNTs is 970.17 m 2 /g, 869.25 m 2 /g and 831.80 m 2 /g, respectively.…”
Section: Characterization Of Carbon Nano-adsorbentmentioning
confidence: 99%
“…Adsorbents based on functional nanomaterials, such as metal oxide nanoparticles [ 81 ], carbon-based nanomaterials (carbon nanotubes, graphene, etc.) [ 82 , 83 ], noble metal nanoparticles [ 84 ], MOFs [ 85 ], and nanocellulose [ 86 ], have attracted much attention as “nanotools” for environmental remediation, taking advantage of their high surface area with reactive sites, fast adsorption kinetics, and possibility of tailoring to obtain specific affinity toward targeted analytes. In the recent years, COFs have emerged as advanced nanomaterials for the adsorption and removal of environmental pollutants [ 22 , 87 ].…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…A broad range of heavy metals generally present in different industrial wastewater, which is toxic to human health and also responsible for the contamination of other environments (Jaishankar et al 2014). Apart from many conventional treatment methods, various nanomaterials are also applied for the removal of heavy metals (Kahrizi et al 2016, Baby et al 2019. Nanomaterials are considered to be very efficient and prominent in the elimination of environmental contaminants (Selvi et al 2019).…”
Section: Application Of Nanomaterials In Heavy Metals Removalmentioning
confidence: 99%